The question of democratic party political system of the Republic of Kazakhstan and Japan. - Ashinova., Zh. Y. (Journal of Oriental Studies, 2016)
In this paper we attempt a comparative analysis of party systems of modern Kazakhstan and Japan in the context of the process of political modernization